Risk Factors for African Swine Fever in Smallholder Pig Production Systems in Uganda - Dione, M. M.; Akol, J.; Roesel, K.; Kungu, J.; Ouma, E. A.; Wieland, B.; Pezo, D. (Transboundary and emerging diseases, 2017)
Smallholder pig production in Uganda is constrained by poor management and high disease burden, with African swine fever (ASF) being one of the most important contributors. However, data to develop appropriate evidence-based disease mitigating interventions along the pig value chain are lacking. This study aimed at determining risk factors associated with the occurrence of outbreaks of ASF in selected districts. A cross-sectional survey of 1195 pig-keeping households in three districts was carried out between April and July 2013. Households were classified into one of three value chain domains (VCDs) based on where the production was located and where most of the products were sold: rural-rural (R-R), ruralurban (R-U) and urban-urban (U-U). Findings revealed that crop farming is the most common primary activity in the R-R and R-U VCDs, while pig keeping was the most common primary activity in the U-U VCDs. Pigs are mostly kept tethered or left to roam in the R-R and R-U VCDs, while in the U-U VCDs, they are mostly confined in corrals. Nearly 20% of the farmers whose farms were hit by an ASF outbreak subsequently sold all their pigs (healthy and sick) to the market in panic. Factors that positively correlated with recent ASF outbreaks were prompt disposal of dead pigs on farms (P < 0.001, OR = 2.3), wild animals present in the village (P < 0.001, OR = 1.7) and farmers sourcing drugs from stockists (P < 0.001, OR = 1.6); while protective factors were the presence of perimeter fences (P = 0.03, OR = 0.5), attendance of farmers at secondary-school level and above (P < 0.001, OR = 0.6), routine cleaning of the pig pens (P < 0.001, OR = 0.6) and pigs being the only livestock kept by farmer (P = 0.01, OR = 0.7). Given the current situation, there is a need to raise awareness among farmers and other value chain actors of biosecurity measures and create incentives for farmers to report ASF cases.
Keywords: African swine fever; Biosecurity; Pig; Value chain; Uganda